QUANTIFYING LITERARY WORKS: IS IT POSSIBLE? - Yayuk Widyastuti Herawati; Siti Masitoh ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
The traditional study of literature has predominantly relied on qualitative methods, such as close reading and interpretive analysis. However, with the advent of digital humanities and advanced computational techniques, scholars are increasingly exploring quantitative approaches to literary analysis. This research delves into the feasibility of quantifying literary works, examining both the potential and the limitations of such methods. Through a comprehensive review of existing literature and methodologies, this study aims to provide a balanced perspective on the intersection of quantitative and qualitative literary analysis.